Price level and brand knowledge and its effects on purchase behavior - De Toni, Deonir; Tormen, Andressa; Milan, Gabriel Sperandio; Eberle, Luciene; Lazzari, Fernanda; Graciola, Ana Paula (Revista de Administração da UFSM, 2021)
Purpose: this study aims to examine the impacts of price levels, high level vs. low level, associated to a known brand vs. an unknown brand over fairness perception, symbolism quality and purchase intention. Design/methodology/approach: one pre-experiment is conducted with a 2 (high price level vs. low price level) x 2 (known brand vs. unknown brand) between-subjects design and a sample of 152 jeans customers. Finding: the results indicate that different price levels with brand knowledge or without brand knowledge impact differently over customer behavior, mainly when it comes to quality, fairness, perceived value, symbolic value and purchase intention of the investigated product and that that the relation between symbolic value and purchase intention is totally mediated by the perceived fairness. Practical Implication: by understanding how customers integrate, relate and infer quality, fairness and symbolic aspects to products through their perceptions concerning price levels and brand knowledge levels, it is possible to supply marketing professionals with information that lead to better-informed choices about pricing policy and branding in their companies. Originality/value: among these research contributions, we emphasize the proposition of eleven research hypotheses that aim to better understand customer behavior from the manipulation of two variables: product price level and brand knowledge level and its impact on perceived quality, fairness, symbolism and purchase intention.